Tikrar al-Muhyi: Development of a Pocketbook for Memorizers of the Qur'an - Niken Sylvia Puspitasari; Ahmad Fadly Rahman Akbar; Alivia Bunga Cahyani (Universitas Ahmad Dahlan, 2022)
Memorizing the Quran preserves its authenticity. During al-Qur'an memorization, a hafizh may face obstacles that make it difficult to memorize the verses. Forgetting memorized verses when adding new ones, many similar verses, lack of focus due to environmental factors, changing al-Qur'an manuscripts, and rarely reading verses to be memorized are obstacles in murojaah. This research aims to develop learning media in the form of pocketbook Tikrar al-Muhyi as an easy solution to murajaah al-Qur'an. This research uses the R&D method, which adopts the development of Borg & Gall. Subjects in this study were students of the University of Darussalam Gontor. Data Collection using questionnaires given to subject material experts, media experts, and students to test the feasibility of the media learning pocketbook. The research findings show that the development of this book is very feasible, with a percentage of 80% based on media and material experts. Furthermore, the eligibility increase was 94% after the second stage test. This research has contributed to Islamic education, especially about media that makes it easier to memorize the al-Qur'an.